Clonal Hematopoiesis of Indeterminate Potential and Cardiometabolic Disease: Challenges, Controversies and Future Perspectives - Anastasiou, Ioanna A.; Kounatidis, Dimitris; Vallianou, Natalia G.; Rebelos, Eleni; Karampela, Irene; Dalamaga, Maria (MDPI, 2026)
Clonal hematopoiesis of indeterminate potential (CHIP) is defined by the expansion of hematopoietic stem cells harboring leukemogenic mutations in the absence of overt malignancy. Strongly associated with advancing age, CHIP is detected by next-generation sequencing of peripheral blood in more than 20% of individuals over 80, most commonly through mutations in DNMT3A, TET2, ASXL1, and PPM1D. While CHIP confers over a four-fold increased risk of hematologic malignancy, it has recently emerged as a key determinant of cardiometabolic health. Epidemiological data indicated a 40% higher cardiovascular disease (CVD) risk events and a 34% increase in all-cause mortality among CHIP carriers, with specific mutations and larger clone sizes conferring greater cardiovascular burden. Preclinical studies have shown that macrophages deficient in TET2 or DNMT3A drive interleukin (IL)-1β/IL-6 inflammasome activation, thereby promoting atherosclerosis and metabolic dysfunction, whereas the JAK2V617F mutation accelerates thrombosis. CHIP integrates into a broader network of dysregulation encompassing adiposity and inflammaging, which underlies its association with diverse comorbidities, including type 2 diabetes (T2D), chronic kidney disease (CKD), and chronic obstructive pulmonary disease (COPD). Multi-omics approaches have identified epigenetic and proteomic signatures correlated with CHIP expansion, providing potential biomarkers for risk stratification. Despite growing evidence of its systemic impact, CHIP screening remains limited to research settings. Emerging therapeutic strategies, including inflammasome inhibition, STING modulation, and epigenetic restoration, highlight its potential as a modifiable risk factor. This narrative review synthesizes current epidemiological, mechanistic, and translational insights, framing CHIP as an emerging causal factor in cardiometabolic disease and as a promising target for precision medicine in aging populations.